Monocytic Tissue Transglutaminase in a Rat Model for Reversible Acute Rejection and Chronic Renal Allograft Injury - Anna Zakrzewicz; Srebrena Atanasova; Winfried Padberg; Veronika Grau (Hindawi Limited, 2015)
Acute rejection is a major risk factor for chronic allograft injury (CAI). Blood leukocytes interacting with allograft endothelial cells during acute rejection were suggested to contribute to the still enigmatic pathogenesis of CAI. We hypothesize that tissue transglutaminase (Tgm2), a multifunctional protein and established marker of M2 macrophages, is involved in acute and chronic graft rejection. We focus on leukocytes accumulating in blood vessels of rat renal allografts (Fischer-344 to Lewis), an established model for reversible acute rejection and CAI. Monocytes in graft blood vessels overexpress Tgm2 when acute rejection peaks on day 9 after transplantation. Concomitantly, caspase-3 is activated, suggesting that Tgm2 expression is linked to apoptosis. After resolution of acute rejection on day 42, leukocytic Tgm2 levels are lower and activated caspase-3 does not differ among isografts and allografts. Cystamine was applied for 4 weeks after transplantation to inhibit extracellular transglutaminase activity, which did, however, not reduce CAI in the long run. In conclusion, this is the first report on Tgm2 expression by monocytes in vivo. Tgm2 may be involved in leukocytic apoptosis and thus in reversion of acute rejection. However, our data do not support a role of extracellular transglutaminase activity as a factor triggering CAI during self-limiting acute rejection.